A growth mechanism for carbon nanotubes using metal oxides as catalysts. (21st May 2018) - Wahab, Hassan; El Gomati, Mohamed M.; Hinder, Steven J.; Watts, John F.
Abstract : Metal oxides have only recently begun to be used as catalysts for the growth of carbon nanotubes. Here, we propose a new model for the growth of carbon nanotubes, based on the intra‐granular charge transfer transition and the lattice strain of the catalyst nanoparticles. This is supported by results obtained from the doped metal oxides like samarium doped zinc oxide (SmZnO) and terbium doped zinc oxide (TbZnO). The intragranular charge transfer transition is believed to be responsible for the dissociation of the hydrocarbon molecules. The lattice strain of the catalyst nanoparticles appears to be responsible for the diffusion of carbon atoms through the catalyst particles.